The effect of mass loss on mechanic properties of heat-treated paulownia wood - Kaygın, Bülent; Gündüz, Gökhan; Aydemir, Deniz; Kaygın, Bülent; Aydemir, Deniz (Wood Research, 2009)
In this study, the eff ect of mass loss on mechanic properties of Paulownia (Paulownia elongata) wood was investigated. For this study, three diff erent temperatures (160, 180, and 200oC) and durations (3, 5, and 7 hours) were carried out. After heat treatment, the mass loss of the heat-treated samples were found and then it is determined how aff ected on mechanic properties of Paulownia wood Th e data obtained were analyzed using variance analysis, and then Tukey’s test was used to determine the eff ect on mechanic properties of mass loss during heat treatment. Th e results show that mechanic properties were occurred decreasing in variation ration in relate with mass loss. While the maximum mass loss found was 9,78% at 200 oC and 7 hour, the compression strength, modulus of elasticity, bending strength and impact strength decreased about 17, 19, 78 and 88%, respectively. Hence, it is determined that the mass loss on mechanic properties of Paulownia wood signifi cantly aff ected.
Keywords: Paulownia wood; Mechanical properties; Mass loss; Heat treatment